2014
DOI: 10.1038/srep07434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in let-7/Lin28 modulate the risk of oral cavity cancer in a Chinese Han Population

Abstract: Let-7 and Lin28 establish a double-negative feedback loop to affect several biological processes, such as differentiation of stem cell, invasion and metastasis, and tumorigenesis. In this study, we systematically investigated the associations between 6 potentially functional SNPs of let7 and Lin28 genes and the risk of oral cavity cancer with a case-control study including 384 oral cavity cancer cases and 731 controls. We found that the variant allele (T) of rs221636 of Lin28B was significantly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Accumulating evidence has revealed essential clues regarding LIN28B expression and potential roles in oral cancers [ 19 , 20 ]. We have revealed a functional single nucleotide polymorphism [variant allele (T) of rs221636] in LIN28B,which is significantly associated with oral cancer susceptibility in a Chinese population, thus supporting the key roles of LIN28B during oral tumorigenesis [ 21 ]. However, the expression pattern of LIN28B and its clinicopathological significance in OSCC have not been definitively established yet.…”
Section: Introductionmentioning
confidence: 86%
“…Accumulating evidence has revealed essential clues regarding LIN28B expression and potential roles in oral cancers [ 19 , 20 ]. We have revealed a functional single nucleotide polymorphism [variant allele (T) of rs221636] in LIN28B,which is significantly associated with oral cancer susceptibility in a Chinese population, thus supporting the key roles of LIN28B during oral tumorigenesis [ 21 ]. However, the expression pattern of LIN28B and its clinicopathological significance in OSCC have not been definitively established yet.…”
Section: Introductionmentioning
confidence: 86%
“…In a study conducted in China, Zhang et al explored association between six genetic variants in let‐7/Lin28 and oral cavity cancer risk with 384 cases and 731 controls, and they detected a protective effect of LIN28B rs221636 on oral cavity cancer. However, they failed to observe the association with the risk of oral cavity cancer for LIN28A rs4659441 and rs3811463 . Sung et al conducted a two genome‐wide association study in East Asian with 5066 breast cancer cases and 4337 controls involving Koreans and Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, later studies indicated that LIN28B rs314276 C>A polymorphism, which is included in our current study, is associated with timing of puberty [27], growth in height from birth to adulthood [28], finger-length ratio [29], growth in height from birth to adulthood [28], childhood obesity and age at menarche [30], and central precocious puberty and early puberty in girls [31]. Moreover, this variant was also found to be associated with the risk and survival of cancer, such as epithelial ovarian cancer [32], colon cancer [33,34], non-small cell lung cancer [35], oral cavity cancer [36], and neuroblastoma [16]. LIN28B protein was found to be unregulated in colon tumours, and the overexpression correlated with reduced patient survival and increased probability of tumour recurrence [34,37]; besides, LIN28B can promote migration, invasion, and malignant transformation of cells [38].…”
Section: Discussionmentioning
confidence: 99%